2018
DOI: 10.1111/1365-2656.12902
|View full text |Cite
|
Sign up to set email alerts
|

Distance–decay differs among vertical strata in a tropical rainforest

Abstract: Biodiversity patterns in horizontal space were not consistent across vertical space, suggesting that canopy fauna may not play by the same set of "rules" as their conspecifics living below them on the ground. Our study provides compelling evidence that the above-ground amphibian assemblage of tropical rainforests is the primary driver of the classical distance-decay relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…Complementarily, we found that the spatial dissimilarity of ant community composition was slightly higher in the litter than in the canopy. Indeed, it is known that the species dissimilarity concerning geographic distances could be dependent on which vertical strata the community live, for instance, for amphibians (Basham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Complementarily, we found that the spatial dissimilarity of ant community composition was slightly higher in the litter than in the canopy. Indeed, it is known that the species dissimilarity concerning geographic distances could be dependent on which vertical strata the community live, for instance, for amphibians (Basham et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Complementarily, we found that the spatial dissimilarity of ant community composition was slightly higher in the litter than in the canopy. Indeed, it is known that the species dissimilarity concerning geographic distances could be dependent on which vertical strata the community live, for instance, for amphibians (Basham et al., 2019). Importantly, our study provides data over the effect of vertical stratification at the plot scale, rather than long geographic distances (e.g., Silva et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We surveyed for frogs during the wet season (April-December) and dry season (January-March; Figure S2). Using survey methods in Scheffers et al (2013) and Basham et al (2018), we conducted vertical, ground-to-canopy surveys for amphibians, with each survey centred on a single canopy tree. Tree selection was randomized;…”
Section: Vertical Stratification Of Amphibiansmentioning
confidence: 99%
“…Indeed, diverse factors all stratify to some degree ranging from leaf area and vegetation connectivity (Arruda et al, 2016;Clark, Olivas, Oberbauer, Clark, & Ryan, 2008) to air turbulence and wind speed (Parker, 1995;Poggi, Porporato, Ridolfi, Albertson, & Katul, 2004). As a result, there are well-documented patterns showing biological communities, across diverse taxa, being structured by these climate and resource gradients in vertical space (Ashton et al, 2016;Basham, Seidl, Andriamahohatra, Oliveira, & Scheffers, 2018;Beaulieu et al, 2010;Chmel, Riegert, Paul, & Novotný, 2016;De Frenne et al, 2019;Schleuning et al, 2011;Stork, Stone, & Sam, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Distance–decay relationships are well documented in a multitude of plant and animal communities (e.g., multiple aquatic taxa, Astorga et al., 2012; tropical amphibians, Basham et al., 2019; multiple taxa, Soininen et al., 2007; urban plants, Sorte et al., 2008). Nonetheless, these relationships are of particular interest to microbial ecologists, because microorganisms were assumed to have ubiquitous distributions for several reasons.…”
Section: Introductionmentioning
confidence: 99%